Student Learning Activeness: An Experimental Study on the Effectiveness of the 9E Learning Cycle Model - Meldayani, Susi; Farida, Farida; Azizah, Nurul; Saputra, M.Indra; Kuswanto, Riyan Terna (Journal of Educational Sciences, 2025)
Learning activeness is essential for achieving optimal educational outcomes. However, many students still demonstrate low levels of active participation, particularly in Islamic Religious Education. The Learning Cycle 9E model is considered a potential strategy to enhance learning activeness through structured learning stages. This study aims to examine its effectiveness in improving students' learning activeness at SMA Negeri 15 Bandar Lampung. This research employs a quantitative approach with a quasi-experimental design. The population consists of all 12th-grade students, with class XII F7 as the experimental group and class XII F8 as the control group, selected through simple random sampling. Normality tests show significance values of 0.92 (experimental) and 0.649 (control), both greater than 0.05, indicating normal data distribution. The t-test results show a significance value of 0.962 (>0.05), leading to the acceptance of H0. Findings indicate that the Learning Cycle 9E model does not significantly impact students' learning activeness. Other factors, such as motivation, classroom environment, and teacher involvement, may influence the results. Further research should explore modifications to the model or alternative cooperative learning strategies to optimize learning activeness in Islamic Religious Education.